Greetings in Malay in Balai Pungut Village, Pinggir District, Bengkalis Regency - Alfiah, Lia; Shomary, Sudirman (UIR Press, 2026)
This research is motivated by the importance of using greetings as part of the communication system. Greetings not only function as a means of greeting, but also reflect social relations, kinship, and the cultural development of the local community. The development of the times also influences changes in the form of greetings used by the millennial generation, thus causing a shift in meaning and usage. Based on this, this research formulates two main problems, namely: (1) what is the form of greetings in the Malay language of Balai Pungut Village, and (2) how greetings change in the community. The purpose of this research is to describe the form of greetings and analyze the changes that occur in their use. This research is useful theoretically as a contribution to linguistic studies, especially morphology and greeting systems, and practically can be a consideration for educators, researchers, and readers in understanding the dynamics of the Sakai Malay language. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and recording techniques with informants who are native residents of Balai Pungut Village. The data obtained were transcribed, classified, and analyzed using Malay greeting theory. The analysis techniques included data reduction, data presentation, and conclusion drawing. Data validity was tested using source and time triangulation. The results showed that greetings among the Malay community of Balai Pungut Village consist of two main categories: kinship greetings (blood and marriage) and non-kinship greetings (customs, religion, and general). There are 18 forms of greetings based on blood or descent, 7 forms of greetings based on marriage, 12 forms of non-kinship greetings, and 25 forms of greeting changes. Furthermore, changes in greetings were found as a result of social interaction, modernization, and the influx of foreign cultures, for example, the change from